Brain Informatics International Conference, BI 2012, Macau, China, December 4-7, 2012, Proceedings - Zanzotto, Fabio; Tsumoto, Shusaku; Taatgen, Niels; Yao, Yiyu Y.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International Conference on Brain Informatics, BI 2012, held in Macau, China, in December 2012. The 34 revised full papers  were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections  on computer science, information technology, artificial intelligence, web intelligence, cognitive science, neuroscience, medical science, life science, economics, data mining, data and knowledge engineering, intelligent agent technology, human computer interaction, complex systems, and system science.
Thinking and Perception-Centric Investigations of Human Information Processing System -- Associative Information Processing in Parahippocampal Place Area (PPA): An fMRI Study -- Language Acquisition Is an Optimized Process Balanced between Holistic and Compositive -- Object Recognition Test in Peripheral Vision: A Study on the Influence of Object Color, Pattern and Shape -- Basic Level Advantage during Information Retrieval: An ERP Study -- A Skill Learning during Heuristic Problem Solving: An fMRI Study -- The Role of Category Label in Adults’ Inductive Reasoning -- Estimation of Visual Feedback Contribution to Limb Stiffness in Visuomotor Control -- Rule Acquisition in the Proceeding of Heuristic Sudoku Solving -- BatGaze: A New Tool to Measure Depth Features at the Center of Gaze during Free Viewing -- A Brain Informatics Approach to Explain the Oblique Effect via Depth Statistics -- An Agent Model for Temporal Dynamics Analysis of a Person with Chronic Fatigue Syndrome -- A Na¨ıve Hypergraph Model of Brain Networks -- The Effect of Individual Psychological Characteristics on Creativity Revelation: Emphasis with Psychological Empowerment and Intrinsic Motivation -- Information Technologies for the Management, Use, and Simulation of Brain Data -- Modeling and Optimization of Information Retrieval for Perception-Based Information -- Sleep Physiological Dynamics Simulation with Fuzzy Set -- Parallels between Machine and Brain Decoding -- Detecting Emotion from EEG Signals Using the Emotive Epoc Device -- An Efficient Visibility Graph Similarity Algorithm and Its Application on Sleep Stages Classification -- Information-Theoretic Based Feature Selection for Multi-Voxel Pattern Analysis of fMRI Data -- Applications -- Multiplications of EEG Samples through Replicating, Biasing, and Overlapping -- The Impact of PSO Based Dimension Reduction on EEG Classification -- Modified Shared Circuits Model for Manufacturing Processes Control: From Psychology and Neuroscience to a Computational Solution -- A Brain-Inspired Computational Model of Emotion and Attention Interaction -- Chinese Medicine Formula Network Analysis for Core Herbal Discovery -- An EEG-Based Brain Informatics Application for Enhancing Music Experience -- Decoding of EEG Activity from Object Views: Active Detection vs. Passive Visual Tasks -- A Cognitive Architecture Based on Cognitive/Neurological Dual-System Theories -- Special Session on Granular Computing and Brain Informatics -- Preliminary Study Using Granular Computing for Remote Sensing Image Segmentation Involving Roughness -- Semi-supervised Clustering via Constrained Symmetric Non-negative Matrix Factorization -- Granular Association Rule Mining through Parametric Rough Sets -- Comparison of Granular Computing Models in a Set-Theoretic Framework -- Multiple Representations of Web Content for Effective Knowledge Utilization -- Rule Measures Tradeoff Using Game-Theoretic Rough Sets -- A Comparison Study of Cost-Sensitive Classifier Evaluations.
Keywords: Artificial intelligence; Application software; Algorithms; Database management; Optical data processing; Pattern recognition; Artificial Intelligence; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Database Management; Image Processing and Computer Vision; Pattern Recognition